Uncovering the Yeast Communities in Fungus-Growing Ant Colonies - Bizarria, Rodolfo [UNESP]; de Castro Pietrobon, Tatiane [UNESP]; Rodrigues, Andre [UNESP] (Springer Nature, 2022)
Yeast-insect interactions are compelling models to study the evolution, ecology, and diversification of yeasts. Fungus-growing (attine) ants are prominent insects in the Neotropics that evolved an ancient fungiculture of basidiomycete fungi over 55–65 million years, supplying an environment for a hidden yeast diversity. Here we assessed the yeast diversity in the attine ant environment by thoroughly sampling fungus gardens across four out of five ant fungiculture systems: Acromyrmex coronatus and Mycetomoellerius tucumanus standing for leaf-cutting and higher-attine fungicultures, respectively; Apterostigma sp., Mycetophylax sp., and Mycocepurus goeldii as ants from the lower-attine fungiculture. Among the fungus gardens of all fungus-growing ants examined, we found taxonomically unique and diverse microbial yeast communities across the different fungicultures. Ascomycete yeasts were the core taxa in fungus garden samples, with Saccharomycetales as the most frequent order. The genera Aureobasidium, Candida, Papiliotrema, Starmerella, and Sugiyamaella had the highest incidence in fungus gardens. Despite the expected similarity within the same fungiculture system, colonies of the same ant species differed in community structure. Among Saccharomycotina yeasts, few were distinguishable as killer yeasts, with a classical inhibition pattern for the killer phenotype, differing from earlier observations in this environment, which should be further investigated. Yeast mycobiome in fungus gardens is distinct between colonies of the same fungiculture and each ant colony harbors a distinguished and unique yeast community. Fungus gardens of attine ants are emergent environments to study the diversity and ecology of yeasts associated with insects.
Keywords: Attine ants; Biodiversity; Killer yeasts; Yeast ecology; Yeast-insect interactions